EFFECT OF SELECTED ACROBATICS GYMNASTICS TRAINING PROTOCOL ON BALANCE APPLIED ON JUNIOR ARTISTIC GYMNASTICS GIRLS - Das, Arup; Sarkar, Susanta (International Journal of Psychosocial Rehabilitation, 2019)
Background:Balance is factor that is basic to performance and especially to high complex movement (It may define as one’s ability to maintain the body’s centre of supporting base of the body). We need balance as we habituated to perform lots of physical movement to accomplish the daily assignment. Objectives: The purpose of the study was to effect of selected acrobatics gymnastics training on Balance. Method: Fifteen girls’ students were selected as the subject for this study. All the students resided in their own organization in the district of Nadia. The age limit of the students was 16 years. Balance was analyzed by specific test for balance referred by Strok Stand test. Results: Result revealed that after six week acrobatics Gymnastics training the strok stand balance performing for static balance for boys is gradually increasing. FatmaÇelikKayapnar (2011) this study aimed at evaluating the effect of movement education program on static balance skills of preschool children (5 7 years). Conclusion: The results tell us that movement education program which was implemented, positively affected static balance of preschool children.